Ricochet Word Sonnets - Sonnets d'un mot - Mayne, Seymour (University of Ottawa Press, 2011)
Ricochet is a bilingual collection of word sonnets by one of the chief innovators of the form, Seymour Mayne. It includes three sequences of pithy and evocative poems that encapsulate moments of sharp perception while also drawing attention to instants of humour that suddenly appear in daily life. Concise and visual in effect, word sonnets are fourteen line poems, with one word per line. Frequently allusive and imagistic, they can also be irreverent and playful. While informed by other short poetry forms such as the Haiku, Mayne's word sonnets are deeply influenced by the Talmudic tradition of maxims, proverbs and images that instruct and inform everyday life. Presented with an excellent translation of the poems into French, Ricochet is a unique volume that showcases this innovative new form. The collection also includes a short preface by the poet and an introductory essay by the translator on the challenges of translating word sonnets. - Ricochet est un recueil bilingue de sonnets d'un mot écrits par l'un des principaux innovateurs de cette forme poétique, Seymour Mayne. On y trouve trois séries de poèmes piquants et évocateurs, qui recèlent des moments de perception aiguë, tout en attirant l'attention sur des instants d'humour surgissant tout à coup dans la vie quotidienne. Les sonnets d'un mot sont des poèmes de quatorze lignes, concis, ayant un mot par ligne, et à l'effet visuel certain. Souvent elliptiques et imagés, ils s'avèrent aussi parfois irrévérencieux et taquins. Bien qu'inspirés par d'autres formes de courts poèmes, comme le haïku, les sonnets de Seymour Mayne sont profondément liés à la tradition talmudique des maximes, proverbes et images qui éclairent la vie quotidienne. Présentant une excellente traduction des poèmes en français, Ricochet est un livre unique qui met en valeur cette nouvelle forme littéraire. L'ouvrage comprend également une courte préface du poète et une introduction de la traductrice sur les défis que comporte la traduction de sonnets d'un mot.